Trade unions in renewal : a comparative study - Fairbrother, Peter; Yates, Charlotte A. B. (Employment and work relations in context., 2003)
This comprehensive survey of continuity and change in trade unions looks at five primarily English-speaking countries: the USA, Canada, Australia, New Zealand and the UK. The authors consider the recent re-examination by trade union movements of the basis of union organization and activity in the face of a harsher economic and political climate. One of the impetuses for this re-examination has been the recent history of unions in the USA. American models of renewal have inspired Australia, New Zealand and the UK, while Canada has undergone a cautious examination of the US model with an attempt.